Ciclaje de nutrientes en áreas cultivadas con arroz en rotación con soya bajo el sistema de siembra directa, en Los Ríos - Álvarez Rodríguez, Roddy Franklin (2021)
The rice crop (Oryza sativa) deserves to be highlighted for being one of the most consumed cereals in the world, it also contributes 20% of calories. It is estimated that by 2030 consumer demand will be approximately 5 billion, the same that has to be satisfied from non-renewable natural resources, such as soil and water. However, soils suitable for rice cultivation are characterized by having low organic matter content and being exposed to degradation. However, soil management techniques are currently being adapted to improve its quality, reduce environmental impact and maximize the productivity of rice cultivation. Given the above, the following bibliographic work aimed to demonstrate the effect of nutrient cycling on the quality of soils dedicated to the production of rice in rotation with soybeans, in a direct sowing system. Thus, it was determined that keeping crop residues on the soil surface contributes to the accumulation of organic carbon in the surface horizon and of nutrients. In addition to improving the physical-chemical attributes of the soil in the medium term.